Land Registration as a Legal Construction of Law in Order to Facing Asean Economic Communities - Sri Ahyani (UIN Sunan Gunung Djati Bandung, 2018)
This article discusses the land registration as a legal construction of law in order to facing Asean economic communities The problems in this study are: (1) What is the Government's policy in solving the problem of land registration in Indonesia so that it can provide certainty for the business world in increasing domestic investment in welcoming the ASEAN Economic Community? (2) How is the implementation of state policies in land registration to provide an investment climate with legal certainty related to land issues? This research uses a normative juridical approach, by analyzing and interpreting theoretical matters concerning principles, conceptions, theories and legal norms relating to land registration. The results of the study show that the government needs to create legal certainty regarding land issues so that it can provide investment excitement for the business world in increasing domestic investment in the atmosphere of the ASEAN Economic Community. The guarantee of legal certainty to be realized in this land registration includes certainty of the status of land rights, certainty of legal subjects, and certainty of legal objects.